Manifestations of Tradition Objection among the Bataks - Hermina Sutami (HISKI, 2008)
This paper tries to find out kinds of emotions appearing from the novel Penakluk Ujung Dunia (Conqueror of the World's Cape). lt told us about the struggle for land among Batak ethnic groups near Lake Toba a long time ago, triggered by the population growth. One ethnic group defeated another under a young commander, Ronggur. They did not only seize the enemies teritory, but also their women and children. One of them, Tio, became Ronggur's slave. He actually disagreed with the way of enlarging territory by attacking others. He believed—he got it from his dream—that someone had asked him to go along the river to its end to find a